Low Voltage Ride-Through Capability Solutions for Permanent Magnet Synchronous Wind Generators - Victor F. Mendes; Frederico F. Matos; Silas Y. Liu; Allan F. Cupertino; Heverton A. Pereira; Clodualdo V. De Sousa (Energies, 2016)
Due to the increasing number of wind power plants, several countries have modified their grid codes to include specific requirements for the connection of this technology to the power system. One of the requirements is the ride-through fault capability (RTFC), i.e., the system capability to sustain operation during voltage sags. In this sense, the present paper intends to investigate the behavior of a full-converter wind generator with a permanent magnet synchronous machine during symmetrical and asymmetrical voltage sags. Two solutions to improve the low voltage ride-through capability (LVRT) of this technology are analyzed: discharging resistors (brake chopper) and resonant controllers (RCs). The design and limitations of these solutions and the others proposed in the literature are discussed. Experimental results in a 34 kW test bench, which represents a scaled prototype of a real 2 MW wind conversion system, are presented.